2017
DOI: 10.1105/tpc.17.00010
|View full text |Cite
|
Sign up to set email alerts
|

Subgenome Dominance in an Interspecific Hybrid, Synthetic Allopolyploid, and a 140-Year-Old Naturally Established Neo-Allopolyploid Monkeyflower

Abstract: Recent studies have shown that one of the parental subgenomes in ancient polyploids is generally more dominant, having retained more genes and being more highly expressed, a phenomenon termed subgenome dominance. The genomic features that determine how quickly and which subgenome dominates within a newly formed polyploid remain poorly understood. To investigate the rate of emergence of subgenome dominance, we examined gene expression, gene methylation, and transposable element (TE) methylation in a natural, <1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
229
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 223 publications
(255 citation statements)
references
References 102 publications
(114 reference statements)
5
229
3
Order By: Relevance
“…), and the ecological preference of L. inaequibasis for stone crevices is also similar to that of L. waltonii . Recent genetic and genomic studies of allopolyploid species have demonstrated that contributions from the maternal and paternal progenitors to the polyploid are rarely equal and can be biased at the genome, gene, or expression level (Yoo & al., ; Edger & al., ; Wang & al., ). Paternal subgenomes of the allopolyploid L. inaequibasis may generally be more dominant in the gene expression patterns of this polyploid species, but further studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…), and the ecological preference of L. inaequibasis for stone crevices is also similar to that of L. waltonii . Recent genetic and genomic studies of allopolyploid species have demonstrated that contributions from the maternal and paternal progenitors to the polyploid are rarely equal and can be biased at the genome, gene, or expression level (Yoo & al., ; Edger & al., ; Wang & al., ). Paternal subgenomes of the allopolyploid L. inaequibasis may generally be more dominant in the gene expression patterns of this polyploid species, but further studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Even more striking is the fact that in our study, global gene expression was not affected by whole genome duplication. Several previous studies have reported genetic and epigenomic processes being disrupted after hybridisation and polyploidisation, with subsequent changes in gene expression (Qi et al, 2012; Renny-Byfield et al, 2014; Khalil et al, 2015; Edger et al, 2017 and references therein). These studies were not performed on meiotic tissue, however given the known failure of meiosis in wheat-rye hybrids and the relatively normal meiotic progression in the duplicated triticale, it would have been reasonable to expect an effect on the expression pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the world’s most important crops, including wheat, rapeseed, sugarcane and cotton, are relatively recent allopolyploids; and much of the current knowledge about WGD is due to research involving these crop species. Several studies have reported major changes in transcription in somatic tissues following polyploidisation (Renny-Byfield et al, 2014 and references therein; Li et al, 2014; Edger et al, 2017). However, there have been very few previous reports on the effects of polyploidisation on transcription during meiosis, a critical stage in the establishment of a polyploid (Braynen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported that the expression dominance is established in the first generation hybrid of two Mimulus species [72], and the dominantly expressed subgenome is linked with lower levels of TE abundance and CHH methylation near the genes. However, the subgenomic expression dominance in interspecific hybrids or allopolyploids can depend on the tissues or organs examined during growth and development [18].…”
Section: Nonadditive Gene Expression and Epigenetic Regulation In Intmentioning
confidence: 99%